Sodium bicarbonate improves swimming performance - Lindh, A. M.; Peyrebrune, M. C.; Ingham, S. A.; Bailey, D. M.; Folland, J. P. (International Journal of Sports Medicine, 2008)
Sodium bicarbonate ingestion has been shown to improve performance in single-bout, high intensity events, probably due to an increase in buffering capacity, but its influence on single-bout swimming performance has not been investigated. The effects of sodium bicarbonate supplementation on 200 m freestyle swimming performance were investigated in elite male competitors. Following a randomised, double blind counterbalanced design, 9 swimmers completed maximal effort swims on 3 separate occasions: a control trial (C); after ingestion of sodium bicarbonate (SB: NaHCO3 300 mg · kg-1 body mass); and after ingestion of a placebo (P: CaCO3 200 mg · kg-1 body mass). The SB and P agents were packed in gelatine capsules and ingested 90 - 60 min prior to each 200 m swim. Mean 200 m performance times were significantly faster for SB than C or P (1 : 52.2 ± 4.7; 1 : 53.7 ± 3.8; 1 : 54.0 ± 3.6 min : ss; p < 0.05). Base excess, pH and blood bicarbonate were all elevated pre-exercise in the SB compared to C and P trials (p < 0.05). Post-200 m blood lactate concentrations were significantly higher following the SB trial compared with P and C (p < 0.05). It was concluded that SB supplementation can improve 200 m freestyle performance time in elite male competitors, most likely by increasing buffering capacity.